What is IoT? (O'Reilly, 2018)
"In this introductory level course designed for business managers and executives, technology guru Emmanuel Henri explores and de-mystifies the IoT--AKA, the Internet of Things. He defines the concepts, technologies, and challenges that underlie the IoT; explores the many ways it's deployed today; outlines the toolsets used to create IoT products; and describes the methods successful businesses use to develop and manage their IoT initiatives."--Resource description page